Status, Change, and Futures of Zooplankton in the Southern Ocean - Johnston, Nadine M.; Murphy, Eugene J.; Atkinson, Angus; Constable, Andrew J.; Cotté, Cédric; Cox, Martin; Daly, Kendra L.; Driscoll, Ryan; Flores, Hauke; Halfter, Svenja; Henschke, Natasha; Hill, Simeon L.; et al. (Frontiers in Ecology and Evolution, 2022)
In the Southern Ocean, several zooplankton taxonomic groups, euphausiids, copepods, salps and pteropods, are notable because of their biomass and abundance and their roles in maintaining food webs and ecosystem structure and function, including the provision of globally important ecosystem services. These groups are consumers of microbes, primary and secondary producers, and are prey for fishes, cephalopods, seabirds, and marine mammals. In providing the link between microbes, primary production, and higher trophic levels these taxa influence energy flows, biological production and biomass, biogeochemical cycles, carbon flux and food web interactions thereby modulating the structure and functioning of ecosystems. Additionally, Antarctic krill (Euphausia superba) and various fish species are harvested by international fisheries. Global and local drivers of change are expected to affect the dynamics of key zooplankton species, which may have potentially profound and wide-ranging implications for Southern Ocean ecosystems and the services they provide. Here we assess the current understanding of the dominant metazoan zooplankton within the Southern Ocean, including Antarctic krill and other key euphausiid, copepod, salp and pteropod species. We provide a systematic overview of observed and potential future responses of these taxa to a changing Southern Ocean and the functional relationships by which drivers may impact them. To support future ecosystem assessments and conservation and management strategies, we also identify priorities for Southern Ocean zooplankton research.